PAPARAN DETAIL PENULANGAN BETON TAHAN GEMPA DI SMKN 26 JAKARTA - Sumeru, Indrawati; Pontan, Darmawan; Sari, Feby Kartika; Nugroho, Muhammad Sapto (Indonesian Collaboration Journal of Community Services (ICJCS), 2025)
Indonesia is a geologically active region prone to frequent seismic activity, where numerous significant earthquakes have led to extensive structural damage. Insights gained from both major and minor seismic events have contributed to the continuous refinement of seismic hazard maps and construction regulations in Indonesia (SNI). However, structural failures remain prevalent due to improper implementation of reinforced concrete detailing that does not adhere to established standards. This Community Engagement Program (PKM) aims to enhance students' understanding of earthquake-resistant reinforced concrete detailing at SMKN 26 Jakarta in accordance with SNI 2847:2019. This activity involves the dissemination of regulations related to earthquake-resistant concrete buildings, as well as case studies on building failures due to earthquakes. Evaluation through questionnaires revealed that the initiative effectively strengthened participants' knowledge of the essential role of precise concrete reinforcement detailing in ensuring structural resilience and safety. Through this initiative, students acquire essential knowledge and practical skills to address challenges in the construction industry, particularly in designing and constructing earthquake-resistant structures. This program plays a vital role in strengthening vocational education and equipping future professionals with the expertise needed to meet industry standards and safety regulations